VET in a time of crisis: Building foundations for resilient vocational education and training systems - (:unkn) unknown (My University, 2020)
"This policy brief examines the impact of the COVID-19 crisis on vocational education and training (VET) systems and how VET systems are responding in OECD countries. The brief also presents steps that governments can take in the context of this crisis to build foundations for tomorrow's strong and resilient VET systems." (Editor, BIBB-Doku)
Keywords: S System beruflicher Bildung; I Internationale & regionale Aspekte; Berufsbildungssystem; OECD-Staaten; Pandemie